Unity 3.x scripting : write efficient, reusable scripts to build custom characters, game environments, and control enemy AI in your Unity game /: write efficient, reusable scripts to build custom characters, game environments, and control enemy AI in your Unity game. (2012) - Unknown
No abstract available